A new vision for public administration - Goodsell, Charles T. (2006)
Employing the metaphor of human sight, this essay advances a new vision for public administration. It is a departure from past visions in that it asks us to "see" the field from its own viewpoint rather than that of others. First, three common perspectives on public administration are critiqued as possessing a vision of the field that is not in accord with its core contributions to the democratic republic. Second, a new vision is advanced comprising three elements: a concept of government-based yet nongovernmental governance in which the contributions of administration are fully accounted for; a trajectory image of the administrative agency propelled by a strong sense of mission; and the notion that administration's highest purpose is to build the public trust that makes democracy possible. - Reproduced.
Keywords: Public administration